Narativ Review: Hubungan Dukungan Sosial Suami Dan Strategi Coping Terhadap Konflik Peran Ganda Pada Bidan - Devi Rachmani, Lailatul (Jurnal Syntax Fusion, 2022)
In this modern era, it is not only men who play a role in work, but women also take part and contribute to work. Women who have a dual role between working and taking care of the household are vulnerable to experiencing stressful situations and existing problems. Social support from husbands shows a significant correlation in making women have good coping strategies in dealing with problems or stressful situations in taking care of the household or work.